Wild and cultivated olive tree genetic diversity in Greece: a diverse resource in danger of erosion - Tourvas, Nikolaos; Ganopoulos, Ioannis; Koubouris, Georgios; Kostelenos, George; Manthos, Ioannis; Bazakos, Christos; Stournaras, Vasileios; Molassiotis, Athanassios; Aravanopoulos, Filippos (Frontiers in Genetics, 2023)
The genetic relationships between Greek wild olive tree populations and cultivars were investigated. A total of 219 wild genotypes and 67 cultivar genotypes were analyzed by employing 10 SSR markers. Data evidenced that the wild populations exhibited high levels of genetic diversity and exclusively host 40% of the total number of alleles detected. Inbreeding was observed within populations, probably as a consequence of their fragmented spatial distribution. The genetic differentiation between cultivars and wild individuals, as well as within wild populations, was low. Nevertheless, three gene pools of wild trees were detected, corresponding to the geographical areas of Northeastern Greece, Peloponnese-Crete and Epirus. Most cultivars clustered in a separate group, while the rest of them formed a heterogenous group with membership coefficients akin to the three wild olive clusters. Regarding the history of olive cultivation in Greece, bidirectional gene flow was detected between populations of Peloponnese-Crete and the gene pool that composes some of Greece's most important cultivars, such as "Koroneiki" and "Mastoidis", which is inferred as an indication of a minor domestication event in the area. A strategy for the protection of Greek-oriented olive genetic resources is proposed, along with suggestions for the utilization of the genetically diverse wild resources with regard to the introgression of traits of agronomical interest to cultivars.